2018
DOI: 10.33254/piaz.35.5
|View full text |Cite
|
Sign up to set email alerts
|

Nove spoznaje o kronologiji groblja batina – sredno na početku starijega željeznog doba

Abstract: Jedno od najznačajnijih nalazišta na jugu Karpatske kotline za kraj kasnoga brončanog i početak starijega željeznog doba predstavlja Batina (Kiskőszeg). Iz Batine je već više od stoljeća poznat niz iznimnih nalaza, danas pohranjenih u nekoliko europskih muzejskih zbirki, za koje se pretpostavlja kako potječu iz uništenih grobnih cjelina, a poslužili su u kronološkom definiranju razvoja daljske grupe. S ciljem određivanja položaja groblja daljske grupe u Batini, proveden je sustavni terenski pregled čiji su rez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…91 A recent LiDAR survey has revealed that the fort covers an area of 4.6 ha, with measurements of either 200 x 226 or 215 x 215 m. The survey has changed 89 Hršak 2016; Los 2016. 90 Bojčić et al 2009;Bojčić et al 2011a;Bojčić et al 2011b;Mušič, Vukmanić 2011;Hršak et al 2013a;Hršak et al 2013b;Hršak et al 2014a;Hršak et al 2014b;Mušič, Vukmanić 2014;Hršak et al 2018. 91 Leleković 2021, 78−89. the initial view on the site. 92 Although the fort's name remains uncertain, some scholars speculate it might have served as a legionary camp for Legio VI Herculia during the Late Roman period, given its strategic importance and large size.…”
Section: Colony's Territory and Limesmentioning
confidence: 99%
See 1 more Smart Citation
“…91 A recent LiDAR survey has revealed that the fort covers an area of 4.6 ha, with measurements of either 200 x 226 or 215 x 215 m. The survey has changed 89 Hršak 2016; Los 2016. 90 Bojčić et al 2009;Bojčić et al 2011a;Bojčić et al 2011b;Mušič, Vukmanić 2011;Hršak et al 2013a;Hršak et al 2013b;Hršak et al 2014a;Hršak et al 2014b;Mušič, Vukmanić 2014;Hršak et al 2018. 91 Leleković 2021, 78−89. the initial view on the site. 92 Although the fort's name remains uncertain, some scholars speculate it might have served as a legionary camp for Legio VI Herculia during the Late Roman period, given its strategic importance and large size.…”
Section: Colony's Territory and Limesmentioning
confidence: 99%
“…2.112. 7 Radman-Livaja,Dizdar 2010, 48, 54. 8 Bulat 1977a Tonc, Filipović 2010, 504, 506-511.9 Pinterović 2014, 83−84; Göricke-Lukić 2018, 90−91.…”
mentioning
confidence: 99%
“…32 Therefore, Aelia Mursa had curtain walls with inner towers for defence. During an excava- 27 Filipović 2005b;Filipović, Katavić 2006a;Filipović, Katavić 2006b;Filipović 2007c;Filipović 2008a;Filipović 2008b;Filipović 2008c;Sunko et al 2008;Vodička Miholjek 2008;Zubčić 2008;Filipović 2009a;Filipović 2010a;Hršak, Vukmanić 2010;Rajković 2011;Vukmanić 2011;Filipović 2012a;Filipović 2012b;Zubčić 2013;Crnković, Filipović 2014;Nađander 2014. 28 Bulat 2001 the map published in Gaćina, Ivanković 1996, 37.…”
Section: Aelia Mursa Intra Murosmentioning
confidence: 99%
“…u tumačenju društvenoga statusa u obzir su uzimani izuzetni metalni predmeti kojih u grobovima daljske grupe nema u većem broju te broj keramičkih posuda (vinski-gasparini 1983: 610;Metzner-Nebelsick 2002: 179-181). Istraživanjem većega broja grobova u Doroslovu (trajković 2008: 19), Sotinu (Ložnjak Dizdar et al 2018) i Batini (Bojčić et al 2018) te provedbom analiza funkcionalnih podataka iz grobova, otvaraju se mogućnosti za detaljnije interpretacije grobova te analize identiteta i statusa pojedinca u zajednicama starijega željeznog doba.…”
Section: History Of Researchunclassified
“…when interpreting social status, the researchers considered exceptional metal objects, which are rare in the Dalj group graves, and the number of ceramic vessels (vinski-gasparini 1983: 610;Metzner-Nebelsick 2002: 179-181). the exploration of the large number of graves in Doroslovo (trajković 2008: 19), Sotin (Ložnjak Dizdar et al 2018), and Batina (Bojčić et al 2018), and the analyses of functional data from the graves, have opened possibilities for more detailed interpretations of the graves and for analyses of identities and statuses of individuals in Early Iron Age communities.…”
Section: Sotin Grobmentioning
confidence: 99%